EDUCATION SYSTEM IN THE TIME OF THE PROPHET MUHAMMAD SAW SUCH AS THE ROLE OF THE KUTTAB AND MOSQUES AS EDUCATION CENTERS - Dewi Candra; Abdusima Nasution (Rahis Cendekia Indonesia, 2024)
The education system during the time of the Prophet Muhammad SAW had a very important role in shaping the character and morals of Muslims. At that time, education was carried out with a very integral approach, not only covering aspects of religious knowledge, but also moral and social aspects. One of the most prominent educational institutions during the Prophet's time was Kuttab, which functioned as a place to teach reading, writing, as well as basic religious knowledge such as the Koran and Hadith. Apart from that, the mosque also functions as a very strategic educational center, not only as a place of worship, but also as a place to study religious, social and cultural knowledge. In the mosque, the Prophet Muhammad SAW conveyed Allah's revelations, taught his friends, and provided guidance in various aspects of life. With this approach, education during the time of the Prophet Muhammad SAW succeeded in creating a society that had strong religious knowledge, noble morals, and was able to adapt to the times. This article will examine in more depth the role of Kuttabs and Mosques as centers of education during the time of the Prophet Muhammad SAW and their impact on the development of the Islamic education system that exists today.